Treat-and-extend therapy using intravitreal aflibercept for neovascular age-related macular degeneration: 2-year real-world practice data from Slovenia - Jaki Mekjavić, Polona (BMC Ophthalmol, 2018)
BACKGROUND: To assess visual outcomes over 24 months in patients with neovascular age-related macular degeneration (nAMD) who initiated intravitreal aflibercept therapy under a treat-and-extend (TE) regimen in real-world settings. METHODS: In this retrospective, observational, multicentre study in Slovenia, medical records of all treatment-naïve patients with nAMD who started intravitreal aflibercept therapy between October 2013 and April 2015 were reviewed. The primary outcome measure was change in mean visual acuity (VA) from baseline to 24 months in patients who received the TE regimen for 2 years, assessed by standardised Early Treatment Diabetic Retinopathy Study charts and calculated as least-squares means. Other outcome measures included the numbers of injections and visits at 12 months and 24 months. RESULTS: The primary analysis included 115 eyes of 105 patients who received TE treatment for 2 years (Group A). The mean VA improved from 57.9 ± 14.9 letters at baseline to 64.6 ± 15.8 letters (+ 6.5 letters, p < 0.0001) at 12 months and 64.8 ± 15.6 letters (+ 7.0 letters, p < 0.0001) at 24 months. The mean number of injections per eye was 8.4 ± 1.9 and the mean number of visits was 8.8 ± 1.7 at 12 months; these numbers decreased to 6.1 ± 2.0 and 6.4 ± 1.9, respectively, at 24 months. The additional analysis included 33 eyes of 33 patients who received TE treatment in Year 1, followed by pro re nata treatment in Year 2 (Group B). Compared with Group A whose vision improvement was maintained at 24 months, the VA gain in Group B eyes seen at 12 months (change in mean VA vs baseline: + 6.9 letters, p = 0.0008) was no longer present at 24 months (change in mean VA vs baseline: + 1.2 letters, p = 0.5733). CONCLUSIONS: Using the TE regimen in clinical practice, intravitreal aflibercept significantly improved visual outcomes in treatment-naïve patients with nAMD, which were maintained over time. TE therapy with intravitreal aflibercept is a rational long-term strategy that can produce favourable outcomes in clinical practice.